SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN MENU MAKANAN SEHAT MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - wulandari, syafitri; Satria Wira Yudha (CV. Hawari, 2021)
Food is one of the important elements that affect health. Eating healthy foods will have a positive impact on the body, one of which can avoid various health problems. People's incomprehension about healthy food menus resulted in the decision-making process of choosing healthy food menus rarely noticed. Decision Support System (SPK) can help the community in making decisions, so they do not feel hesitant in choosing a menu, and the information is also more accurate. In the process of data processing, this system uses the Simple Additive Weighting (SAW) method. The SAW method is used to determine the exact healthy food menu based on the criteria and weights that have been determined. The decision support system to determine healthy food menus using the Simple Additive Weighting (SAW) method helps the community in determining a good food menu by providing healthy food recommendations for the community in the form of food rankings based on predetermined weights.